2020
DOI: 10.3390/su122410554
|View full text |Cite
|
Sign up to set email alerts
|

Communication Strategies for the 2030 Agenda Commitments: A Multivariate Approach

Abstract: Companies are fully aware of the importance of including the Sustainable Development Goals (SDGs) in their corporate social responsibility (CSR) strategies, and of the importance of ensuring that the information disclosed allows groups to be identified. The business contribution to the 2030 Agenda is of interest, as it entails an accurate representation of company identity and is congruent with its contribution to the 2030 Agenda. For it, a content analysis of the business communication of 69 Spanish companies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 67 publications
2
17
0
Order By: Relevance
“…According to the theory of social psychology, self-verification is typical of managers who want to be known and understood by others according to their firm beliefs and feelings about themselves, including their sense of self and self-esteem. Similar results were obtained by Phan et al [91], García-Sánchez et al [92], Melón-Izco et al [93], Capela-Borralho et al [94] and Parra-Domínguez et al [95], authors who found the existence of a neutral discourse when companies report on their commitments to the 2030 Agenda, the content of management report or a CSR coupling in the case of family firms reporting.…”
Section: Discussion Of Resultssupporting
confidence: 81%
“…According to the theory of social psychology, self-verification is typical of managers who want to be known and understood by others according to their firm beliefs and feelings about themselves, including their sense of self and self-esteem. Similar results were obtained by Phan et al [91], García-Sánchez et al [92], Melón-Izco et al [93], Capela-Borralho et al [94] and Parra-Domínguez et al [95], authors who found the existence of a neutral discourse when companies report on their commitments to the 2030 Agenda, the content of management report or a CSR coupling in the case of family firms reporting.…”
Section: Discussion Of Resultssupporting
confidence: 81%
“…However, the underlying business motives for CSR disclosure are characterised by a high degree of ambiguity due to the consideration of possible use of CSR as a mechanism to manipulate external opinions regarding the company's behaviour or to manage relations with a specific group of stakeholders (i.e., García-Sánchez et al 2020c).…”
Section: Theoretical Framework and Research Hypothesismentioning
confidence: 99%
“…Secondly, this study contributes to the family business literature by focusing on the decisions that these companies make about the relevance of the information they disclose and the adequacy to their CSR actions. Family researchers have currently focused on the analysis of family groups either in CSR practices (i.e., Berrone et al 2010;Cruz et al 2014;Cuadrado-Ballesteros et al 2017;García-Sánchez et al 2020c) or in corporate transparency (i.e., Cuadrado-Ballesteros et al 2015;Gavana et al 2017;Bansal et al 2018). This paper is the first article that combines these two research lines.…”
Section: Introductionmentioning
confidence: 99%
“…The UN considers that the implementation of the 2030 Agenda requires the intense participation and engagement of governments, the private sector (microenterprises, multinational companies, and cooperatives), and civil society. In addition, the UN conceives organizations as key players in achieving the SDGs, both locally and internationally [57,58]. This initiative urges organizations to adopt a set of universal principles on human rights, labor rights, the environment, and the fight against corruption, through a voluntary commitment to social responsibility and ethics, as reflected in the SDG Compass Guide for business action on the SDGs [59].…”
Section: Strategic Management Of Csr: Models Regulations Legislation and Guidelinesmentioning
confidence: 99%